Programa de atividades recreativas para aprendizagem de leitura e escrita: contextualização das palavras ensinadas - Lima, Débora Corrêa de (Universidade Federal de São Carlos, 2009)
The goal of this study was to develop a program of object-playing tasks to teach nameobject relations, and to verify its effects on learning reading and writing. To teach reading participants were exposed to a computerized teaching program based on the stimulus equivalence paradigm. Thirteen students, aged seven to ten years old, participated in both teaching and object-playing tasks. These tasks were organized in three conditions. Condition one (Object) taught objects naming and the second Condition (Ilustration) taught pictures naming. In both conditions, the tasks made use of words that were taught in the reading and writing procedure. The third condition (Control) taught picture naming as well; however, these pictures were different from those used in the teaching program. Nine words were taught, three familiar, three nonfamiliar and three pseudo-words. The object-playing tasks were always completed before the teaching phases that targeted non-familiar and pseudo-words. Four students were assigned to the Object Condition, four were assigned to the Illustration Condition, and five were assigned the Control Condition. A multiple baseline design across words was used for the analysis of individual performances in reading acquisition. The number of assessment sessions varied across participants, from 11 to 54 sessions. This meant that participants had to be exposed to many sessions of retraining. It was observed that, regardless the teaching condition, the number of teaching sessions was fewer for learning familiar words than it was for learning non-familiar and pseudo words, which suggests that familiarity is a relevant variable in the reading acquisition. All participants learned to name the objects or pictures that represented the aimed words of this study, implying that object-playing tasks were efficient to teach the name-object relations. However, the results did not indicate differences between Object and Illustration conditions concerning reading acquisition. These results also suggest that the material format did not have a critical influence on the number of assessment sessions completed by participants. Instead, the critical variable on reading acquisition was the establishment of matching printed to dictated words from which reading emerged.
Keywords: Leitura - estudo e ensino; Leitura e escrita; Aprendizagem; Material técnico - pedagógico - confecção; Equivalência de estímulos; Aquisição de vocabulário; Familiaridade; Reading and writing learning; Object-playing tasks; Stimulus equivalence; Vocabulary; Familiarity; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL